Developing algorithm for object tracking using passive sensors - Cheam, S.-R. (IEEE Computer Society, 2014)
Object tracking is a vital feature in autonomous navigation involving multiple vehicles, e.g. platooning and tethering. For high speed platooning, advanced sensors like laser range finder or camera are usually employed. Due to their relatively low cost, passive sensors are used for collision avoidance of near objects. Their uses can be further expanded as a backup system for object tracking or obstacle avoidance. This paper describes the development of object tracking algorithm which in turns implemented on a low speed tethering using two mobile robots. Â© 2014 IEEE.